Reusing Test Cases Based on the Function Point - 张娟 童维勤 蔡立志 黄文彬 HWANG Jenq-Neng (东华大学学报（英文版）, 2014)
Reusing test cases from existing test case library is quite common in the software testing field. Testing practice tells us that there is a strong relationship between the granularity of a function unit under testing and that of the test case. A function unit with small granularity usually results in the test cases with the same small granularity. Therefore a test case defined as the function point,i. e.,the smallest size function unit,was provided for the first time.Though test cases with smaller granularity usually have better reusability,the cost of accurately reusing and integrating such test cases is also higher. In order to balance the test case reusability and the cost of test case reuse,a novel test case reuse model based on the function point was proposed in this paper. In this model,a reusable test case for specification-based testing was defined and some reuse strategies and three formal reuse methods were given. Finally,the complete automatic software process was realized by a reusing generation tool. The new method has improved reuse accuracy,while greatly enhances the software productivity.